Evaluation of chemical restraint, isoflurane anesthesia and methadone or tramadol as preventive analgesia in spotted pacas (Cuniculus paca) subjected to laparoscopy - Uscategui, Ricardo AR. [UNESP] (2021)
Objective: To evaluate the efficacy and cardiopulmonary effects of ketamine–midazolam for chemical restraint, isoflurane anesthesia and tramadol or methadone as preventive analgesia in spotted pacas subjected to laparoscopy. Study design: Prospective placebo-controlled blinded trial. Animals: A total of eight captive female Cuniculus paca weighing 9.3 ± 0.9 kg. Methods: Animals were anesthetized on three occasions with 15 day intervals. Manually restrained animals were administered midazolam (0.5 mg kg–1) and ketamine (25 mg kg–1) intramuscularly. Anesthesia was induced and maintained with isoflurane 30 minutes later. Tramadol (5 mg kg–1), methadone (0.5 mg kg–1) or saline (0.05 mL kg–1) were administered intramuscularly 15 minutes prior to laparoscopy. Heart rate (HR), respiratory rate, mean arterial pressure (MAP), peripheral oxygen saturation (SpO2), end-tidal CO2 partial pressure (PE′CO2), end-tidal concentration of isoflurane (FE′Iso), pH, PaO2, PaCO2, bicarbonate (HCO3−), anion gap (AG) and base excess (BE) were monitored after chemical restraint, anesthesia induction and at different laparoscopy stages. Postoperative pain was assessed by visual analog scale (VAS) for 24 hours. Variables were compared using ANOVA or Friedman test (p < 0.05). Results: Chemical restraint was effective in 92% of animals. Isoflurane anesthesia was effective; however, HR, MAP, pH and AG decreased, whereas PE′CO2, PaO2, PaCO2, HCO3− and BE increased. MAP was stable with tramadol and methadone treatments; HR, FE′Iso and postoperative VAS decreased. VAS was lower for a longer time with methadone treatment; SpO2 and AG decreased, whereas PE′CO2, PaCO2 and HCO3− increased. Conclusions and clinical relevance: Ketamine–midazolam provided satisfactory restraint. Isoflurane anesthesia for laparoscopy was effective but resulted in hypotension and respiratory acidosis. Tramadol and methadone reduced isoflurane requirements, provided postoperative analgesia and caused hypercapnia, with methadone causing severe respiratory depression. Thus, the anesthetic protocol is adequate for laparoscopy in Cuniculus paca; however, methadone should be avoided.